2018
DOI: 10.1039/c7cp06987a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different substituents of methyl 5-R-salicylates on the excited state intramolecular proton transfer process

Abstract: The proton transfer reaction in methyl 5-R-salicylate is found to be highly sensitive to the presence of specific substituents in resonance with the hydroxyl group, leading to different fluorescence behaviors of methyl 5-R-salicylate with different substituents (J. Catalán, J. Phys. Chem. B, 2015, 119, 2132). But a detailed survey of its reaction mechanism is lacking. In our research, the hydrogen bond strengthening behavior in excited states is affected by the different substituents that have been reported fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…Thus, determining the potential energy barrier for the ESIPT process is crucial under different conditions. Generally, the theoretical investigations provide direct approaches to solve this problem in recent years . The overall ESIPT reaction is complicated, and unraveling the detailed mechanism of ESIPT seems to be more and more important experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, determining the potential energy barrier for the ESIPT process is crucial under different conditions. Generally, the theoretical investigations provide direct approaches to solve this problem in recent years . The overall ESIPT reaction is complicated, and unraveling the detailed mechanism of ESIPT seems to be more and more important experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…Proton transfer (PT) reaction has been highly concerned by experimental and theoretical researchers because of its significance in many chemical and biological phenomena . A large number of studies on excited‐state intermolecular reaction (ESPT) have been widely reported in order to abstract the useful information and to control such reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Given various photochemical phenomena (i.e., quenching of fluorescence, shifts of spectra, charge transfer, and so on) involved in the hydrogen bond, [11][12][13][14][15][16] more and more researchers are paying attention to excited-state hydrogen bonding interactions and dynamics. As one of the most correlative hydrogen bonding dynamics in both biological and chemical processes, [17][18][19][20][21][22][23] excited-state intramolecular proton transfer (ESIPT) should be prevalent in nature. [24,25] From both experimental and theoretical viewpoints, [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] ESIPT has currently become a hot research topic.…”
Section: Introductionmentioning
confidence: 99%
“…During the past several decades, ESIPT molecules have attracted considerable attention due to their tremendous applications in diverse fields, such as fluorescence probes, fluorescence sensors, organic lasers, organic light emitting diodes, optical storage, molecular switches, and others. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Because of the wide applications based on ESIPT reaction, the kinetic processes and reaction mechanisms have currently become particularly significant. To further research this kind of reaction at the theoretical level, density functional theory (DFT) and time-dependent density functional theory (TDDFT) methods have become the most popular computing methods to explore elementary cases about electronic structures and electronic states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation